UPAYA MENINGKATKAN PRESTASI BELAJAR PKn MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY PADA SISWA KELAS IV SD NEGERI 007 PUSARAN - Sofian Sofian (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This research is motivated by low student learning activity on Civics lesson. In order to increase studentlearning activities need a model that is cooperative learning model type two stay two stray in fourth gradestudents SD Negeri 007 Pusaran. It aims to know the improvement of learning achievement of Civics after theimplementation of learning model of cooperative learning type TSTS in fourth grade students of SD Negeri 007Pusaran, knowing the influence of learning motivation of Civics after the implementation of learning withcooperative learning model type TSTS in fourth grade students of SD Negeri 007 Pusaran; provides an overviewof appropriate learning methods in an effort to improve student learning achievement and make students becomeactive in teaching and learning activities. This research was conducted in September of odd semester 2016/2017with object of 24 students. The results concluded that: (1) cooperative learning method type TSTS can improvethe quality of learning Civics; (2) cooperative learning method of TSTS type has positive impact in improvingstudents 'learning achievement which is marked by the improvement of students' learning mastery in every cycle,that is cycle I (54.17%), cycle II (91.67%); 3) TSTS type cooperative learning method can make students feelthemselves getting attention and opportunity to express opinions, ideas, ideas, and questions; 4) students canwork independently or in groups, and be able to account for individual or group tasks; and 5) the application ofcooperative learning method type TSTS have positive influence, that is can improve student's learningmotivation.